If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 + -10x = -18 Reorder the terms: 9 + 7x + -10x = -18 Combine like terms: 7x + -10x = -3x 9 + -3x = -18 Solving 9 + -3x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3x = -18 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = -18 + -9 -3x = -18 + -9 Combine like terms: -18 + -9 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| 3+2x=75 | | 2x+1y=1.70 | | 1/x+2/x+1 | | 3x-6=-9+25 | | 4r+9+r=-17-8r | | 5x=-10y+30 | | 7-4d=3d-9d+25 | | 0.333(b-9)=b+9 | | 3/4x=9 | | 7=34 | | -1/4x=7 | | 9(c+2)-11=5(2c+3)-2 | | 3/8x=120 | | y-6=4(x-3)+2 | | -7+x=x/10-6 | | x/3.1=6 | | 15y^2=4-7y | | 8+27w=72w | | (x+4/3)(x-7/3) | | 6d+4d+3= | | 8+27w= | | 2x+7=x+25 | | -7+x=34+2x | | 2/7z=6 | | 13t-(5-2t)=5(3t-1) | | 13x+39=65 | | c/4+7+2 | | 3x+-16=-1 | | 252-4x=41x+17 | | 4/3m=12 | | y=-5x^2-11 | | 9z-18=27 |